2019
DOI: 10.1002/ece3.5870
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance and the elevation ranges of woody plant species in the mountains of Costa Rica

Abstract: Aim To understand how disturbance—here defined as a transient reduction in competition—can shape plant distributions along elevation gradients. Theory suggests that disturbance may increase elevation ranges, especially at the lower range limits, through reduced competitive exclusion. Nevertheless, to date this relationship remains unclear. Location Mountains of Costa Rica. Methods We compared the elevation range of woody stems over 10 cm dbh (“trees”) observed in plots along two transects spanning a range of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…We maintained it for 18 months from February 2017 to August 2018. Temperature declines from an annual mean of 24°C to 10°C from low to high elevation, while precipitation follows a unimodal shape, from around 3400 mm a year at the lowest elevations, then rises until it peaks at almost 4200 mm at 1500 m and then declines again to around 2000 mm at the highest elevations (Muñoz Mazón et al 2019, 2020, Veintimilla et al 2019). The lowest parts of the elevation gradient are ‘premontane forest' a floristic transition between lowland and cloud forest.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We maintained it for 18 months from February 2017 to August 2018. Temperature declines from an annual mean of 24°C to 10°C from low to high elevation, while precipitation follows a unimodal shape, from around 3400 mm a year at the lowest elevations, then rises until it peaks at almost 4200 mm at 1500 m and then declines again to around 2000 mm at the highest elevations (Muñoz Mazón et al 2019, 2020, Veintimilla et al 2019). The lowest parts of the elevation gradient are ‘premontane forest' a floristic transition between lowland and cloud forest.…”
Section: Methodsmentioning
confidence: 99%
“…Building on previous syntheses (Sheil 2016) and pilot studies (Muñoz Mazón et al 2019), these ideas on how forest gaps and clearings shape species ranges complement other studies that examined how climate and biotic interactions shape species distributions (Louthan et al 2015, Defossez et al 2016, Olsen et al 2016, Ettinger and HileRisLambers 2017, Putnam and Reich 2017. While it is well known that species tolerance to drought, low temperatures or frost can influence range limits (Ettinger et al 2011, Anderegg and HilleRisLambers 2015, Korner et al 2016, the role of plant interactions, such as competition and facilitation, are still debated (HilleRisLambers et al 2013, Scherrer et al 2020.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, montane orogenesis led to fluctuations in the climate in high‐altitude regions during the Quaternary period to severely impact the vegetation biota and genetic architecture by preventing population expansion and the migration of species with narrow thermal tolerance ranges (Avise, 2000; Knowles, 2001). Previous highly cited studies broadly explored the effects of tectonic uplifts and climatic oscillations on the diversification patterns of plants species in Europe, North America, and other regions, for example, in the Sierra Madre of Mexico (Bryson et al., 2012), the Andes (Hughes & Eastwood, 2006), Costa Rica (Muñoz et al., 2019), and the Himalayas (Xu et al., 2010; Yang et al., 2012). In China, many previous studies focused on this phenomenon in the complex and conspicuous topographical regions on the Qinghai–Tibet Plateau and adjacent areas (Ding et al., 2020; Wen et al., 2014; Xing & Ree, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In China, many previous studies focused on this phenomenon in the complex and conspicuous topographical regions on the Qinghai–Tibet Plateau and adjacent areas (Ding et al., 2020; Wen et al., 2014; Xing & Ree, 2017). It was recently reported that climate factors and montane orogenesis had strong and direct effects on montane forests, and they shaped the montane plant diversity (Li et al., 2020; Muñoz et al., 2019). However, another critical biodiversity hotspot in central China is the Qinling Mountains (QM), and the detailed evolutionary histories of plant species in this area are generally unknown (Liu et al., 2015; Wan et al., 2016; Zhang et al., 2015).…”
Section: Introductionmentioning
confidence: 99%